Incidence of tuberculosis in advanced lung cancer patients treated with immune checkpoint inhibitors – A nationwide population-based cohort study. (August 2021) - Kim, Hyung Woo; Kim, Ju Sang; Lee, Sang Haak
Highlights: Incidence of tuberculosis in lung cancer patients receiving chemotherapy is high. Immune checkpoint inhibitors did not pose additional risk for tuberculosis among them. Prolonged use of steroid showed a tendency to increase the risk of tuberculosis. Previous history of tuberculosis was a significant risk factor for tuberculosis. Abstract: Objectives: The aim of this study was to investigate the risk of TB in advanced non-small cell lung cancer (NSCLC) patients treated with Immune checkpoint inhibitors (ICI) after a platinum-based chemotherapy. Materials and methods: A nationwide population-based retrospective cohort study using National health insurance dataset was designed. Patients who were diagnosed as lung cancer between September 1st, 2017 and August 31st, 2018 in South Korea were selected. Among them, those with NSCLC who initiated a platinum-based chemotherapy within 3 months were finally included and followed up until December 31st, 2018. Patients who received nivolumab, pembrolizumab, and atezolizumab within study period were classified as the ICI group. Cox proportional hazard model with time-varying covariates was used to determine effects of the duration of conventional chemotherapy, ICI, and consecutive use of systemic steroid on TB. Results: A total of 6335 patients were enrolled with 3568.7 years of total follow-up period. Among them, 899 patients underwent ICI treatment. Within the follow-up period, 15 TB cases were identified in the ICI group (incidence: 2582.5 per 100, 000 person-years) and 63 TB cases were found in the conventional chemotherapy group (incidence: 2108.5 per 100, 000 person-years). In a multivariable Cox proportional hazard model, treatment with ICI was not a significant risk factor for TB development (hazard ratio (HR): 1.21, 95 % confidence interval (CI): 0.45−3.26, p  =  0.700). Instead, prolonged use of steroid was associated with an increased TB risk (HR: 1.91, 95 %CI: 0.89−4.08, p  =  0.095), although its statistical significance was dependent on the operational definition of the effect duration. Previous TB history and older age were independent risk factors for TB disease. Conclusion: In this real-world study, additional treatment with ICI did not increase the risk of TB in advanced NSCLC patients who underwent a cytotoxic chemotherapy. However, TB incidence in these patients was high regardless of ICI treatment. Classifications: Systemic Treatments.